2023
DOI: 10.1038/s41598-023-41797-9
|View full text |Cite
|
Sign up to set email alerts
|

Deploying efficient net batch normalizations (BNs) for grading diabetic retinopathy severity levels from fundus images

Summiya Batool,
Syed Omer Gilani,
Asim Waris
et al.

Abstract: Diabetic retinopathy (DR) is one of the main causes of blindness in people around the world. Early diagnosis and treatment of DR can be accomplished by organizing large regular screening programs. Still, it is difficult to spot diabetic retinopathy timely because the situation might not indicate signs in the primary stages of the disease. Due to a drastic increase in diabetic patients, there is an urgent need for efficient diabetic retinopathy detecting systems. Auto-encoders, sparse coding, and limited Boltzm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 41 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…These pathological damages gradually result in irreversible visual impairment and even blindness. [ 3 ] Studies have indicated that factors such as prolonged duration of diabetes, hypertension, hyperlipidemia, and faster heart rate can increase the likelihood of DR development and worsen prognosis. [ 4 6 ]…”
Section: Introductionmentioning
confidence: 99%
“…These pathological damages gradually result in irreversible visual impairment and even blindness. [ 3 ] Studies have indicated that factors such as prolonged duration of diabetes, hypertension, hyperlipidemia, and faster heart rate can increase the likelihood of DR development and worsen prognosis. [ 4 6 ]…”
Section: Introductionmentioning
confidence: 99%